Teachers’ perceptions of English language teaching process via online learning during Covid-19 - Cut Meurak Bulan Aflah Aksyah; Asnawi Muslem; Saiful Marhaban (English Education Journal, 2021)
During the Covid-19 pandemic, many teachers and students were doing the teaching and learning process from home. They experienced many problems during the remote instruction. Therefore, the objectives of this research were to investigate the teachers' perceptions and obstacles in the process of teaching and learning English by using online learning during the Covid-19 pandemic. The method used in this research was mixed method, combining quantitative and qualitative methods. The instruments used were a set of questionnaire and interview. The data collected from the questionnaire was analyzed using descriptive statistic. In addition, the interview result was analyzed qualitatively to describe the obstacles. The result in the questionnaire indicated that most of the teachers were against the implementation of online learning, i.e. 55.45% and 44.54% teachers were in favor of this method of instruction. The problems can be categorized into technical and situational problems. These problems can be resolved depending on teachers' teaching experience, condition, and situation. Teachers can give the learning module to the students, and the teachers must be creative in delivering the teaching material. In addition, parents' support is very crucial for maintaining students’ motivation, enthusiasm, and expression during online learning.